Sosialisasi Standarisasi Produk UMKM Intan Permata Untuk Meningkatkan Efisiensi Produksi Dan Keberlanjutan Usaha - Alwi, Miftahul Jannah; Islianty, Nur Risky; Niluh Putu Evvy Rossanty; Anisah; Muhammad Isra Iradat (Politeknik Negeri Jember, 2026)
Product standardization socialization for UMKM Intan Permata, which is engaged in the production of batik cloth using eco-print techniques in Matansala Village, Bungku Tengah District, Morowali Regency. To date, UMKM Intan Permata has carried out production without clear SOPs and measurable quality standards. Without standard guidelines, the production process is often inconsistent, which risks producing products with varying quality. This results in the resulting products not always meeting the desired quality standards, thereby reducing customer satisfaction and potential sales. The production process without adequate supervision, the use of raw materials, labor, and time is often inefficient, which also impacts high production costs. This activity is expected to improve production efficiency and business sustainability through the implementation of standardization in their production processes. This activity includes socialization on the importance of product standardization, the creation of Standard Operating Procedures (SOPs), and training in the application of higher quality standards. Thus, it is expected to produce more consistent products, reduce waste, and increase competitiveness in the market. This activity is expected to provide benefits in the form of increased practical skills in the field of business management and production, as well as the ability to implement standardization techniques in daily business.